Hard carbon silicon-based negative electrode material and preparation method and application thereof

By performing two carbon coatings on the surface of silicon particles, the problem of low capacity retention of existing single-layer carbon-covered silicon particle composite materials is solved, and higher conductivity and capacity retention are achieved, which significantly improves the cycle stability of lithium-ion batteries.

CN119673997APending Publication Date: 2025-03-21FUJIAN SHANSHAN TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411812950.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing single-layer carbon-coated silicon-particle composites quickly lose capacity during the initial cycle, resulting in low capacity retention and ineffectively solving challenges such as internal rupture and SEI thickening.

Method used

By performing two carbon coatings on the surface of silicon particles, polyacrylonitrile is used as the carbon source, and a carbon coating treatment is performed first, and then a second carbon coating treatment is performed to form a hard carbon silicon-based negative electrode material.

Benefits of technology

The conductivity and capacity retention rate of the hard carbon silicon-based anode material are improved, and compared with the single carbon coating method, it has higher conductivity and lower impedance, which significantly improves the cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673997A_ABST
    Figure CN119673997A_ABST
Patent Text Reader

Abstract

The invention discloses a hard carbon silicon-based negative electrode material and a preparation method and application thereof. The preparation method of the hard carbon silicon-based negative electrode material comprises the following steps: mixing silicon nanoparticles with a polyacrylonitrile solution A to obtain a mixture A, drying the mixture A, and carbonizing to obtain a primary carbon-coated material; and mixing the primary carbon-coated material with a polyacrylonitrile solution B to obtain a mixture B, drying the mixture B, and carbonizing to obtain the hard carbon silicon-based negative electrode material. According to the hard carbon silicon-based negative electrode material and the preparation method thereof, the surfaces of the silicon particles are subjected to two-time carbon coating, and compared with single-time carbon coating, the obtained hard carbon silicon-based negative electrode material has higher conductivity, lower impedance and higher capacity retention ratio.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hard carbon silicon-based negative electrode material and a preparation method and application thereof. Background Art

[0002] Silicon-based anode materials have attracted increasing attention as promising candidates for next-generation high-energy-density lithium-ion batteries. Compared with graphite, silicon is abundant and has a higher theoretical specific capacity (3578 mAh g−1 vs. 372 mAh g−1). In addition, silicon-based anode materials have a lower working potential (0.2–0.4 V) compared with Li / Li+ as a counter electrode. However, during the charge and discharge process, silicon particles undergo a huge volume change (280%), resulting in continuous fragmentation and recombination of particles during the reaction. This situation leads to irreversible consumption of lithium ions and electrolyte components and increases the battery polarization caused by the thick SEI layer, thereby rapidly reducing the capacity. To address these issues, a variety of methods have been proposed, including the use of nanosized or nanostructured active materials, modified binders, pre-lithiation, additives, and carbon surface coatings. Among them, the carbon coating can be achieved by dispersing silicon particles in a solution containing an organic carbon source (such as asphalt, monosaccharides and polysaccharides or polymers) and subsequent heat treatment.

[0003] Some studies have shown that the use of conductive polymers such as polyacrylonitrile (PAN) or polyaniline (PANi) as carbon sources in silicon-containing composites can improve their capacity retention. PAN is widely used in the industrial field of manufacturing high-strength carbon materials due to its high carbon content and excellent conductivity. When PAN is used to make Si / C composites, cyclization and conjugation reactions will occur after heat treatment between 180°C and 425°C to form linked ring compounds; continuous heating between 425°C and 600°C will cause lateral dehydrogenation and cross-linking; when it exceeds 600°C, the carbonization process is achieved by eliminating nitrogen and volatile compounds. Therefore, PAN is a good choice for the preparation of Si / C composites, and an intrinsically conductive polymer matrix with conjugated double bonds can be obtained at moderate temperatures, or carbonization can be completed at temperatures >600°C. It has also been reported that silicon is dispersed in a PAN solution using a 7:3 (Si:PAN) ratio, and the obtained slurry is cast on a copper current collector, and then the electrode is heat treated at 300°C-500°C to cyclize PAN while avoiding carbonization reactions to achieve an initial specific capacity of 2585mAh / g, and 58% of the capacity is maintained after 150 cycles at 0.1C, which is related to the intrinsic conductivity formed by the delocalized sp2π bonds during the cyclization process and also due to the limited pyrolysis that leaves PAN with residual polymer residues. In addition, there have been studies reporting that the silicon-graphite-polyacrylonitrile composite material synthesized by its researchers, containing 17.5wt.% silicon, was placed in an argon atmosphere at 800°C for 4 hours, and exhibited a reversible capacity of approximately 660mAh g−1 at a cycle rate of 0.25C.

[0004] Although the surface of silicon nanoparticles can be covered with carbon sources such as polyacrylonitrile, many Si / C composites lose capacity rapidly during the initial cycle until a stable specific capacity is reached. This situation shows that simple single-layer carbon coating cannot solve the challenges of internal rupture and SEI thickening to achieve sufficient capacity retention. Summary of the invention

[0005] The present invention aims to solve the problem that the existing single-layer carbon-coated silicon particle composite material has a low capacity retention rate, and further provides a hard carbon silicon-based negative electrode material and a preparation method and application thereof. The hard carbon silicon-based negative electrode material prepared by the present invention has high conductivity and capacity retention rate.

[0006] The present invention solves the above technical problems through the following technical solutions:

[0007] The present invention provides a method for preparing a hard carbon silicon-based negative electrode material, which comprises the following steps:

[0008] (1) mixing silicon nanoparticles with polyacrylonitrile solution A to obtain a mixture A, drying the mixture A and then carbonizing it to obtain a primary carbon-coated material;

[0009] (2) The primary carbon coating material is mixed with polyacrylonitrile solution B to obtain a mixture B, and the mixture B is dried and then carbonized to obtain a hard carbon silicon-based negative electrode material.

[0010] In the present invention, in step (1), the mass ratio of the silicon nanoparticles to the polyacrylonitrile in the polyacrylonitrile solution A is preferably 1:(1-2). If the single coating amount of polyacrylonitrile is too large, a large amount of PAN will also agglomerate and cannot be dispersed and coated on the surface of the silicon particles, hindering the passage of lithium ions and resulting in reduced capacity.

[0011] In the present invention, in step (1), the silicon nanoparticles and the polyacrylonitrile solution A are preferably mixed by heating and stirring.

[0012] The heating temperature for the heating, stirring and mixing is preferably 70-80°C, for example 60°C.

[0013] The stirring speed of the heating, stirring and mixing is preferably 700-900 rpm, for example 800 rpm.

[0014] The heating, stirring and mixing time is determined according to the actual situation, with uniform mixing being the end point, for example, 10 to 14 hours.

[0015] In the present invention, in step (1), carbonization is performed after drying. Compared with direct carbonization, this can avoid the problem that direct carbonization causes the temperature to rise too quickly, causing a large number of bubbles to be generated during the evaporation process of the solvent and fall off the surface of the silicon particles, resulting in poor coating effect.

[0016] The drying temperature of the mixture A is preferably 70-80°C, for example 60°C.

[0017] The drying time of the mixture A is preferably 10 to 14 hours, for example 12 hours.

[0018] In the present invention, in step (1), the temperature of the carbonization treatment is preferably 900-1100°C, for example 1000°C.

[0019] The temperature rise of the carbonization treatment is preferably staged, and the staged temperature rise procedure preferably includes: firstly raising the temperature to 300-400°C, and then raising the temperature to 900-1100°C.

[0020] The heating rate in the first stage is preferably 1-2°C / min.

[0021] The heating rate in the second stage is preferably 8-12°C.

[0022] For example, the temperature is first increased to 300°C at 1°C / min, and then increased to 1000°C at 10°C / min.

[0023] In the present invention, the carbonization treatment time is preferably 1 to 3 hours, for example 2 hours.

[0024] The carbonization treatment is preferably carried out in an inert atmosphere. The inert atmosphere is conventional in the art, such as a nitrogen atmosphere.

[0025] In the present invention, in step (2), the mixing ratio of the silicon nanoparticles in the primary carbon coating material to the polyacrylonitrile in the polyacrylonitrile solution A is preferably 1:(1-3). If the amount of polyacrylonitrile added is too large, the performance of the hard carbon silicon-based negative electrode material is not significantly improved, but the cost is increased.

[0026] In the present invention, in step (2), the mixing method of the primary carbon coating material and the polyacrylonitrile solution B is preferably heating and stirring. The heating temperature of the heating and stirring is preferably 70-80°C, such as 60°C, and the stirring speed of the heating and stirring is preferably 700-900rpm, such as 800rpm.

[0027] In the present invention, in step (2), the drying temperature, drying time, carbonization temperature, carbonization time, carbonization temperature, and carbonization atmosphere of the mixed material B are the same as those of the aforementioned step (1).

[0028] In the present invention, in step (1) and / or step (2), the carbonization treatment may further include washing and drying steps. The washing is performed using a conventional washing liquid in the art, such as alcohol. The drying temperature is conventional in the art, such as 60-80°C.

[0029] In the present invention, the particle size of the silicon nanoparticles is preferably 100-200 nm, which range refers to the fluctuation range of the maximum particle size and the minimum particle size of the silicon nanoparticles. Furthermore, D50 is preferably 150 nm.

[0030] In the present invention, the polyacrylonitrile solution A is preferably formed by dissolving polyacrylonitrile in a solvent.

[0031] The solvent is a conventional solvent in the art that can dissolve polyacrylonitrile, such as dimethyl sulfoxide, DMF or tetrahydrofuran. The purity of the dimethyl sulfoxide is preferably greater than 99.9%.

[0032] Wherein, the mass ratio of the polyacrylonitrile to the dimethyl sulfoxide is preferably 1:(3-5), for example 1:4.

[0033] In the present invention, the polyacrylonitrile solution B is preferably formed by dissolving polyacrylonitrile in a solvent.

[0034] The solvent is a conventional solvent in the art that can dissolve polyacrylonitrile, such as dimethyl sulfoxide, DMF or tetrahydrofuran. The purity of the dimethyl sulfoxide is preferably greater than 99.9%.

[0035] Wherein, the mass ratio of the polyacrylonitrile to the dimethyl sulfoxide is preferably 1:(3-5), for example 1:4.

[0036] In the present invention, preferably, the mass ratio of the silicon nanoparticles in step (1) to the polyacrylonitrile in the polyacrylonitrile solution A is different from the mass ratio of the silicon nanoparticles in the primary carbon-coated material to the polyacrylonitrile in the polyacrylonitrile solution B in step (2). More preferably, the mass ratio of the silicon nanoparticles in step (1) to the polyacrylonitrile in the polyacrylonitrile solution A is 1:(1-2), for example, 1:1, and the mass ratio of the silicon nanoparticles in the primary carbon-coated material to the polyacrylonitrile in the polyacrylonitrile solution B in step (2) is 1:(1-3), for example, 1:3.

[0037] In the present invention, in the polyacrylonitrile solution A or the polyacrylonitrile solution B, the molecular weight of polyacrylonitrile is preferably 100,000-200,000 g / mol, for example 150,000 g / mol.

[0038] The present invention also provides a hard carbon silicon-based negative electrode material prepared by the preparation method of the hard carbon silicon-based negative electrode material.

[0039] The present invention also provides the use of the aforementioned hard carbon silicon-based negative electrode material as a negative electrode material in a lithium ion battery.

[0040] The positive and progressive effects of the present invention are:

[0041] The present invention performs carbon coating twice on the surface of silicon particles. Compared with single carbon coating, the hard carbon silicon-based negative electrode material obtained by the present invention has higher electrical conductivity, lower impedance and higher capacity retention rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 TGA diagrams of different samples.

[0043] Figure 2 The Raman spectra of the samples of various embodiments and comparative examples are shown in FIG.

[0044] Figure 3 The X-ray diffraction patterns of the samples of various embodiments and comparative examples are shown in FIG.

[0045] Figure 4 The conductivity curves of the samples of various embodiments and comparative examples under different pressures.

[0046] Figure 5 The discharge capacity variation curves of various embodiments and comparative examples are shown in FIG.

[0047] Figure 6 The capacity retention rate change curves of various embodiments and comparative examples are shown in FIG. DETAILED DESCRIPTION

[0048] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0049] In the following examples, the molecular weight of polyacrylonitrile is 150,000 g / mol, which is purchased from Mairui Biochemical Technology Co., Ltd., and the purity of dimethyl sulfoxide is >99.9%, which is purchased from Mairui Biochemical Technology Co., Ltd.

[0050] Example 1

[0051] (1) Take a certain amount of PAN (150,000 g / mol) and dissolve it in DMSO (4 times the mass of PAN). After stirring and dissolving, add silicon nanoparticles (1 times the mass of PAN). The particle size of the silicon nanoparticles is 100-200 nm, and the D50 particle size is 150 nm.

[0052] (2) Heat and stir at 60°C and 800 rpm using a magnetic stirrer for 12 h;

[0053] (3) After stirring evenly, place in a vacuum oven and dry at 60°C for 12 hours;

[0054] (4) Take out the dried sample and use a tube furnace to heat it to 300 °C at 1 °C / min under a nitrogen atmosphere, then heat it to 1000 °C at 10 °C / min, keep it at 1000 °C for 2 hours, and then naturally cool it to room temperature;

[0055] (5) Take out the carbonized sample and clean it with alcohol solution;

[0056] (6) After cleaning, the composite material with a single carbon coating layer is obtained by drying in a vacuum oven at 60°C;

[0057] (7) Prepare the same PAN-DMSO solution as in step (1), add the single carbon coating layer sample of step (6) in a ratio of silicon nanoparticles to PAN of 1:1, repeat steps (1) to (6) to obtain a double-coated carbon layer composite material, named Si@DCS-1.

[0058] Example 2

[0059] (1) Take a certain amount of PAN (150,000 g / mol) and dissolve it in DMSO (4 times the mass of PAN). After stirring and dissolving, add silicon nanoparticles (1 times the mass of PAN). The particle size of the silicon nanoparticles is 100-200 nm, and the D50 particle size is 150 nm.

[0060] (2) Use a magnetic stirrer to heat and stir at 60°C and 800 rpm;

[0061] (3) After stirring evenly, place in a vacuum oven and dry at 60°C for 12 hours;

[0062] (4) Take out the dried sample and use a tube furnace to heat it to 300 °C at 1 °C / min under a nitrogen atmosphere, then heat it to 1000 °C at 10 °C / min, keep it at 1000 °C for 2 hours, and then naturally cool it to room temperature;

[0063] (5) Take out the carbonized sample and clean it with alcohol solution;

[0064] (6) After cleaning, the single carbon coating layer sample was obtained by drying in a vacuum oven at 60°C;

[0065] (7) Prepare a PAN-DMSO solution with a mass three times that of PAN in step (1), add the single carbon coating layer sample of step (6) in a ratio of silicon nanoparticles to PAN of 1:3, repeat steps (1) to (6) to obtain a double-coated carbon layer composite material, named Si@DCS-3.

[0066] Comparative Example 1

[0067] (1) Take a certain amount of PAN (150000 g / mol) and dissolve it in DMSO (4 times the mass of PAN). After stirring and dissolving, add silicon nanoparticles (1 times the mass of PAN). The particle size of the silicon nanoparticles is 100-200 nm, and the D50 particle size is 150 nm.

[0068] (2) Use a magnetic stirrer to heat and stir at 60°C and 800 rpm;

[0069] (3) After stirring evenly, place in a vacuum oven and dry at 60°C for 12 hours;

[0070] (4) Take out the dried sample and use a tube furnace to heat it to 300°C at 1°C / min under a nitrogen atmosphere, then heat it to 1000°C at 10°C / min, keep it at 1000°C for 2 hours, and then naturally cool it to room temperature;

[0071] (5) Take out the carbonized sample and clean it with alcohol solution;

[0072] (6) After cleaning, the product was dried in a vacuum oven at 60 °C to obtain a single-coated carbon layer composite material, named Si@SCS-1.

[0073] Comparative Example 2

[0074] (1) Take a certain amount of PAN (150,000 g / mol) and dissolve it in DMSO (4 times the mass of PAN). After stirring and dissolving, add 0.5 times the mass of PAN silicon nanoparticles. The particle size of silicon nanoparticles is 100-200 nm, and the D50 particle size is 150 nm.

[0075] (2) Use a magnetic stirrer to heat and stir at 60°C and 800 rpm;

[0076] (3) After stirring evenly, place in a vacuum oven and dry at 60°C for 12 hours;

[0077] (4) Take out the dried sample and use a tube furnace to heat it to 300°C at 1°C / min under a nitrogen atmosphere, then heat it to 1000°C at 10°C / min, keep it at 1000°C for 2 hours, and then naturally cool it to room temperature;

[0078] (5) Take out the carbonized sample and clean it with alcohol solution;

[0079] (6) After cleaning, the composite material was dried in a vacuum oven at 60 °C to obtain a single-coated carbon layer, named Si@SCS-2.

[0080] Effect Example

[0081] The thermal transformation process from room temperature to 1000°C of pure PAN, PAN+Si composite (i.e., the sample in step 3 of comparative example 2) and PAN+Si@SCS composite (i.e., the sample carried out to step 3 during the second coating in example 1) was analyzed by thermogravimetric analysis (TGA). The amount of PAN used in the three samples was the same.

[0082] The results are as follows Figure 1 As shown, from Figure 1 It can be seen that pure PAN has the largest mass loss, PAN+Si composite has a reduced mass loss, and PAN+Si@SCS composite has an even smaller mass loss. This proves that PAN can retain more substances and reduce volatilization during the carbonization process after mixing with Si. During the secondary coating carbonization process, the mass loss is further reduced, and the carbon shell can better form silicon nanoparticles.

[0083] Figure 2 The Raman spectrum test diagram of each embodiment is shown. It can be seen from the figure that the -1 The sharp peak at 950 cm -1 The broad peak at 1345 cm−1 and 1590 cm -1 The broad peaks at correspond to amorphous carbon (D band) and graphitized carbon (G band), respectively. From the ratio of these two peaks, it can be seen that the composite material prepared by the two-step carbon coating method has a lower degree of graphitization and more carbon defects. The reason is that silicon nanoparticles can catalyze the graphitization of carbon sources and the contact area between the carbon in the second carbon shell and silicon nanoparticles is smaller than that of the first carbon shell. Therefore, the samples using the two-step carbon coating process have more carbon defects and amorphous layers, which increases the contact surface of lithium ions and is conducive to the rapid passage of lithium ions.

[0084] Figure 3 The X-ray diffraction patterns of various examples are shown, from which it can be seen that single carbon coating and double carbon coating do not lead to the formation of electrochemically inactive silicon carbide. In particular, for Example 2, reflections of the carbon 002 face and the 101 face in the carbon shell can be seen.

[0085] Specific surface area test:

[0086] The samples obtained in each embodiment were soaked in 0.25 mol NaOH, with the volume ratio of sample to NaOH being 1:10, and the samples were soaked at room temperature for 48 hours, and the specific surface area after etching away silicon was measured.

[0087] Table 1 shows the specific surface areas of various embodiments, comparative examples and various embodiments after etching away silicon by soaking in NaOH.

[0088] Table 1 Specific surface area

[0089]

[0090] From the results in the table, it can be seen that the specific surface area of ​​the material using the one-step carbon coating process increases after NaOH etching, while the specific surface area of ​​the material using the two-step carbon coating process decreases after NaOH etching. From the results, it can be seen that the silicon exposed on the surface of the silicon-carbon material using the one-step carbon coating process is more corroded and dissolved to produce more pores, reflecting that the one-step carbon coating process cannot well encapsulate silicon nanoparticles, while the silicon-carbon material using the two-step carbon coating process can be well encapsulated by the carbon layer and will not be etched to cause more pores.

[0091] Conductivity test:

[0092] Table 2 and Figure 4 The electrical conductivity of each example and comparative example is shown, and the electrical conductivity of the composite powder was measured by electrochemical impedance spectroscopy (EIS).

[0093] Table 2 Conductivity

[0094]

[0095] As can be seen from the figure, as the pressure increases, the conductivity of the composite materials of the four examples increases linearly due to the compression of the particles. When comparing the composite materials with one-step carbon coating (Comparative Example 1 and Comparative Example 2) and the composite materials with two-step carbon coating (Example 1 and Example 2), it can be observed that the electronic conductivity of the composite materials with higher carbon content increases, which confirms the effect of carbon content on electronic conductivity. Comparative Example 1 has the lowest carbon fraction and shows the lowest conductivity; comparing Comparative Example 2 and Example 1, it is found that the composite materials with two-step carbon coating have higher specific conductivity at the same carbon coating amount; after adding more carbon content to the two-step carbon coating (Example 2), it is found that the conductivity has been improved to a greater extent.

[0096] Battery capacity performance test:

[0097] In order to study the electrochemical properties of the materials in each example, electrodes were prepared using the composite materials prepared in the examples and batteries were assembled. The battery preparation method is as follows:

[0098] A half-cell negative electrode slurry consisting of 80 wt.% active material (i.e., the composite material of the embodiment), 10 wt.% sodium alginate as a binder, 10 wt.% carbon black, and a water-isopropanol mixture as a solvent was used and cast on a 9 μm copper foil using a doctor blade and a film applicator, with a coating thickness of 60 μm. After drying at 40 ° C for 12 hours, a 14 mm disc was used for punching, and then vacuum dried at 120 ° C for 12 hours. The material loading of all electrode coatings was 0.8 ± 0.1 mg / cm 2 CR2032 coin cells were assembled in an argon-filled glove box using five layers of glass fiber separators and lithium sheet counter electrodes, and the electrolyte was prepared by adding 10 wt.% ethylene fluorocarbonate and 2 wt.% ethylene carbonate to LP57.

[0099] Table 3 and Figure 5 The specific charge capacity of each embodiment is shown by constant current and constant voltage cycling measurement of each composite material and Li / Li between 0.01V and 1.5V at a rate of 0.5C.

[0100] Table 3 Cyclic capacity test results

[0101]

[0102] Table 4 and Figure 6 The capacity retention rate of each composite material and Li / Li in each embodiment is shown when constant current and constant voltage cycling is measured between 0.01V and 1.5V at a rate of 0.5C.

[0103] Table 4 Capacity retention test results

[0104]

[0105] Through Table 3 and Figure 5 It can be seen that Comparative Example 1 shows the highest initial lithium removal capacity of 1909.5 mAh / g, while the initial lithium removal capacities of Comparative Example 2 and Example 1 are 1523.3 mAh / g and 1276 mAh / g respectively. Example 2 has the highest carbon fraction and the lowest initial capacity of 946.6 mAh g −1 .

[0106] From Table 4 and Figure 6 It can be seen that the data of the two single-layer carbon-coated composite materials (i.e., Comparative Example 1 and Comparative Example 2) look similar, indicating the same degradation mechanism. This results in that the increase in carbon fraction within the evaluation range does not improve the cycle stability of the composite material (the capacity retention rate of Comparative Example 1 after 100 cycles is 69.1%, and the capacity retention rate of the composite material of Comparative Example 2 is 71.2%). From the composite materials of Comparative Example 2 and Example 1, where the mass ratio of Si to PAN is the same as 1:2, the capacity retention rate of the composite material of Example 1 in the cycle is slightly improved from 71.2% to 74%, and there is a significant improvement in the first 80 cycles. The composite material of Example 2 shows the best performance, with a capacity retention rate of 87.1% after 100 cycles. When comparing the capacity retention of the composite materials of Example 1 and Example 2, the effect of carbon content on the electrochemical properties of the active material becomes obvious, and the better coating of silicon particles in Example 2 enhances the mechanical stability of the composite material.

Claims

1. A method for preparing a hard carbon silicon-based negative electrode material, characterized in that: It includes the following steps: (1) mixing silicon nanoparticles with polyacrylonitrile solution A to obtain a mixture A, drying the mixture A and then carbonizing it to obtain a primary carbon-coated material; (2) The primary carbon coating material is mixed with polyacrylonitrile solution B to obtain a mixture B, and the mixture B is dried and then carbonized to obtain a hard carbon silicon-based negative electrode material.

2. The method for preparing the hard carbon silicon-based negative electrode material according to claim 1, characterized in that: The preparation method of the hard carbon silicon-based negative electrode material meets one or more of the following conditions: ① The mass ratio of the silicon nanoparticles to the polyacrylonitrile in the polyacrylonitrile solution A is 1:(1-2); ② The particle size of the silicon nanoparticles is 100-200 nm, and further, D50 is preferably 150 nm; ③ The mixing method of the silicon nanoparticles and the polyacrylonitrile solution A is heating and stirring mixing, wherein the heating temperature of the heating and stirring mixing is preferably 70~80℃, for example 60℃, the stirring speed of the heating and stirring mixing is preferably 700~900rpm, for example 800rpm, and the heating and stirring mixing time is preferably 10~14h.

3. The method for preparing the hard carbon silicon-based negative electrode material according to claim 1, characterized in that: The preparation method of the hard carbon silicon-based negative electrode material meets one or more of the following conditions: ① The drying temperature of the mixed material A is 70-80°C, for example 60°C; ② The drying time of the mixed material A is 10 to 14 hours, for example 12 hours.

4. The method for preparing the hard carbon silicon-based negative electrode material according to claim 1, characterized in that: The preparation method of the hard carbon silicon-based negative electrode material meets one or more of the following conditions: ① The temperature of the carbonization treatment is 900-1100°C, for example 1000°C; ② The temperature rise of the carbonization treatment is staged heating, and the staged heating program preferably includes: first heating to 300-400°C, and then heating to 900-1100°C. The heating rate of the first stage is preferably 1-2°C / min, and the heating rate of the second stage is preferably 8-12°C. For example, first heating to 300°C at 1°C / min, and then heating to 1000°C at 10°C / min; ③ The carbonization treatment time is 1 to 3 hours, for example 2 hours; ④ The carbonization treatment is carried out in an inert atmosphere, and the inert atmosphere is preferably a nitrogen atmosphere.

5. The method for preparing the hard carbon silicon-based negative electrode material according to claim 1, characterized in that: The preparation method of the hard carbon silicon-based negative electrode material meets one or more of the following conditions: ① In step (2), the mass ratio of silicon nanoparticles in the primary carbon coating material to polyacrylonitrile in the polyacrylonitrile solution B is 1:(1-3); ② The mass ratio of the silicon nanoparticles to the polyacrylonitrile in the polyacrylonitrile solution A in step (1) is different from the mass ratio of the silicon nanoparticles to the polyacrylonitrile in the polyacrylonitrile solution B in the primary carbon-coated material in step (2). Preferably, the mass ratio of the silicon nanoparticles to the polyacrylonitrile in the polyacrylonitrile solution A in step (1) is 1:(1-2), for example, 1:1, and the mass ratio of the silicon nanoparticles to the polyacrylonitrile in the polyacrylonitrile solution B in step (2) is 1:(1-3), for example, 1:3; ③ The mixing method of the primary carbon coating material and the polyacrylonitrile solution B is heating and stirring mixing, wherein the heating temperature of the heating and stirring mixing is preferably 70~80℃, such as 60℃, and the stirring speed of the heating and stirring mixing is preferably 700~900rpm, such as 800rpm.

6. The method for preparing the hard carbon silicon-based negative electrode material according to claim 1, characterized in that: The preparation method of the hard carbon silicon-based negative electrode material meets one or more of the following conditions: ① The drying temperature of the mixed material B is 70-80°C, for example 60°C; ② The drying time of the mixture B is 10 to 14 hours, for example 12 hours.

7. The method for preparing the hard carbon silicon-based negative electrode material according to claim 1, characterized in that: In step (1) and / or step (2), the carbonization treatment further includes washing and drying steps, wherein the washing liquid used in the washing is preferably alcohol, and the drying temperature is preferably 60-80°C.

8. The method for preparing the hard carbon silicon-based negative electrode material according to claim 1, characterized in that: The preparation method of the hard carbon silicon-based negative electrode material meets one or more of the following conditions: ① The polyacrylonitrile solution A is formed by dissolving polyacrylonitrile in a solvent, wherein the solvent is preferably dimethyl sulfoxide, DMF or tetrahydrofuran, and the mass ratio of the polyacrylonitrile to the dimethyl sulfoxide is preferably 1:(3-5), for example 1:4; ② The polyacrylonitrile solution B is formed by dissolving polyacrylonitrile in a solvent, wherein the solvent may be dimethyl sulfoxide, DMF or tetrahydrofuran, and the mass ratio of the polyacrylonitrile to the dimethyl sulfoxide is preferably 1:(3-5), for example 1:4; ③ In the polyacrylonitrile solution A or the polyacrylonitrile solution B, the molecular weight of polyacrylonitrile is 100,000-200,000 g / mol, for example, 150,000 g / mol.

9. A hard carbon silicon-based negative electrode material prepared by the method for preparing a hard carbon silicon-based negative electrode material as claimed in any one of claims 1 to 8.

10. Use of the hard carbon silicon-based negative electrode material as claimed in claim 9 as a negative electrode material in a lithium ion battery.

Citation Information

Cited By

  • Si-coated SiC-coated EG ternary composite material as well as preparation method and application thereof

    CN121439760A